On the number of points included in a plane figure with large pairwise distances : On the number of points included in a plane figure - Agama, Theophilus (My University, 2022)
Using the method of compression we show that the number of points that can be placed in a plane figure with mutual distances at least d > 0 satisfies the lower bound... #find the complete abstract in the attached file
Keywords: plane figure; circumference; compression